Partial characterization of protease from a thermophilic fungus, Thermoascus aurantiacus, and its hydrolytic activity on bovine casein - Merheb, Carolina W.; Cabral, Hamilton; Gomes, Eleni; Da-Silva, Roberto (Elsevier B.V., 2007)
Proteases are one of the most important groups of industrial enzymes, with considerable application in the food industry. The aim of this work was to study a novel protease produced by the thermophilic fungus, Thermoascus aurantiacus, through solid-state fermentation (SSF). The enzyme acted optimally at pH 5.5 and 60 degrees C it was stable up to 60 degrees C for 1 h and in the pH range 3.0-9.5. To elucidate the enzyme's proteolytic activity, its hydrolytic profile on bovine casein, an important protein in the food industry, was studied by enzymatic hydrolysis on skim milk, analyzed by gel electrophoresis (UREA-PAGE), which clearly showed that the protease does not have the same specificity as bovine chymosin. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: SSF; protease; wheat bran; casein; proteolytic activity; characterization; Hydrolysis; electrophoresis